Domestic Protests and Foreign Policy: An Examination of Anti-China Protests in Vietnam and Vietnamese Policy Towards China Regarding the South China Sea. (April 2019) - Hoang, Phuong
Abstract: The Sino-Vietnamese relationship is characterized by asymmetry, yet Vietnam's post-Cold War foreign policy towards China encompasses three paradigms: (a) internal and external balancing against China, (b) greater international integration to prevent political and economic dependence on China and (c) 'cooperation' with China on mutual interests while 'struggling' against China's encroachment on Vietnam's sovereignty. The ongoing dispute in the South China Sea presents a primary security concern for Vietnam as well as a challenge to its bilateral relations with China, particularly as maritime tensions provoke nationalist and anti-China protests among the Vietnamese public. This article presents an analysis of anti-China protests in Vietnam that resulted from South China Sea tensions between 2007 and 2017 in order to examine whether the protests—which are rare in Vietnam—had any effect on Vietnam's foreign policy towards China. The findings reveal that the protests did not result in a change in Vietnam's foreign policy towards China both during the maritime crises or in the long term.